TEKNIK WORD FLOW GAME DALAM MENINGKATKAN KEMAMPUAN MENULIS KALIMAT BAHASA JEPANG (Penelitian Eksperimen Murni Terhadap Siswa Kelas XI SMK 45 Lembang Tahun Ajaran 2017/2018) - Asih, Rusita Puji; Juangsih, Juju; Rasiban, Linna Meilia (Universitas Pendidikan Indonesia (Indonesia University of Education), 2018)
This study aims to determine the improvement of the writing ability Japanese sentences using word flow game technique and how students response about this game technique in Japanese language learning process. This research used true experimental method with control group pretest-posttest design. The sample of the research consists of 32 students of SMK 45 Lembang period 2017/2018, second grade of Tata Busana class and Nursing class, where 16 of them are for experiment class and 16 for control class. The research instruments are test and questionnaire. From the result of the data analysis, the average score of experiment class before the treatment is 37,74 and changed becoming 84,73 after the treatment. With tscore was 4,15 db = 30 in signification degree of 2,04 (5%) and 2,75 (1%). Since the t-score was bigger than t-table, thus the hypothesis is accepted that with using word flow game technique in learning process, student ability to write Japanese sentence become increasing. Based on the result of questionnaire, the writer concluded that more than half of respondents have a thought that word flow game technique is fun and helping in Japanese sentences learning process.